Analisis Ketepatan Waktu Pengiriman Sampel Sputum di UPT Puskesmas Pangala - Norma Oknita; Ana Agung Ayu Eka Cahyani; Putu Gede Subhaktiyasa; Sri Idayani (Inovasi Kesehatan Global, 2026)
Tuberculosis (TB) is one of the oldest infectious diseases that has been present throughout human history and remains a significant public health problem worldwide today. Technological developments have enabled TB detection using the GeneXpert® MTB/RIF Molecular Rapid Test (TCM). Fast and accurate laboratory testing is essential in healthcare services. This study aims to analyze the timeliness of sputum sample delivery at the Pangala Community Health Center (UPT Puskesmas Pangala), using a qualitative research design, namely a descriptive type of research by observing sputum samples stored at the Pangala Community Health Center (UPT Puskesmas Pangala) before being sent to the reference laboratory. The sample in this study was 36 samples taken by total sampling. The results showed that there were 29 samples sent within a period of <7 days and 7 samples sent within a period of 8-14 days. This finding proves that there is inaccuracy in sending sputum samples at the Pangala Community Health Center (UPT Puskesmas Pangala). It is hoped that future researchers can touch on aspects of sample quality such as sample volume, sample color, and sample consistency.